2016
DOI: 10.1002/2016gl068147
|View full text |Cite
|
Sign up to set email alerts
|

Compressible turbulence with slow‐mode waves observed in the bursty bulk flow of plasma sheet

Abstract: In this paper, we report the evidence of compressible turbulence with slow‐mode waves in a bursty bulk flow of plasma sheet. This compressible turbulence is characterized by a multiscale (1–60 s) anticorrelation between plasma density and magnetic field strength. Besides, the magnetic compressibility spectrum stays nearly constant at all the measured frequencies. Furthermore, the turbulence energy distributions are anisotropic with k⊥ > k//, and the dispersion relation is consistent with slow‐mode prediction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Yao et al (2015) used the list of Liu et al (2013) to try to physically explain the dipolarization feature of fast flows. Runov et al (2015) showed that the characteristic timescale of the flux transport enhancements does not depend on geocentric distance and is around 40-60 s. Most recently, Wang et al (2016) found evidence of compressible fluctuations during bursty bulk flows in the plasma sheet.…”
Section: Frühauff and K-h Glassmeier: Magnetotail Fast Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yao et al (2015) used the list of Liu et al (2013) to try to physically explain the dipolarization feature of fast flows. Runov et al (2015) showed that the characteristic timescale of the flux transport enhancements does not depend on geocentric distance and is around 40-60 s. Most recently, Wang et al (2016) found evidence of compressible fluctuations during bursty bulk flows in the plasma sheet.…”
Section: Frühauff and K-h Glassmeier: Magnetotail Fast Flowsmentioning
confidence: 99%
“…The main observation to be made here is that for a good portion of the available events the maximum magnetic field variations are almost parallel to the flow direction, i.e., δB δV . Especially for the downtail region, assuming that the background magnetic field is of Harris sheet nature (Harris, 1962), i.e., the background field being parallel to GSM-X, this indicates a compressional nature of magnetic field variations for the total flow burst event (see also Wang et al, 2016). Still, there are also many events obviously deviating from the flow direction for which a detailed analysis of the database will be necessary.…”
Section: Maximum Variance Directions Of Magnetic Field and Velocity Datamentioning
confidence: 99%
“…So far, the BBF structure has been extensively studied in the MHD regime (Angelopoulos et al, , ; Cao et al, ; Yu et al, ), with particular focus on the flux transport (Angelopoulos et al, , ; J. Liu et al, ), energy conversion (Fu et al, ; Hamrin et al, ), waves/turbulence (Huang et al, ; Vörös et al, ; T. Wang et al, ), particle acceleration (Fu et al, ; Fu, Khotyaintsev, et al, ; Fu, Xu, et al, ; Fu, Cao, et al 2019; Duan et al, ; Liu, Fu, Xu, Cao, et al, 2017; Liu, Fu, Xu, Wang, et al, 2017; Xu, Fu, Liu, et al, 2018; Xu, Fu, Norgren, et al, 2018), substorm activities (Cao et al, ; Juusola et al, ; Ma et al, ), and so forth. A consensus in these studies is that the BBF carries electrons and ion together ( V i = V e ), with the frozen‐in condition well satisfied ( E + V e × B = 0) inside the structure.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the BBF structure has been extensively studied in the MHD regime (Angelopoulos et al, 1992(Angelopoulos et al, , 1994Cao et al, 2006;Yu et al, 2017), with particular focus on the flux transport (Angelopoulos et al, 1992(Angelopoulos et al, , 1994J. Liu et al, 2014), energy conversion Hamrin et al, 2011), waves/turbulence (Huang et al, 2012;Vörös et al, 2006;T. Wang et al, 2016), particle acceleration (Fu et al, 2011;Fu, Xu, et al, 2019;Fu, Cao, et al 2019;Duan et al, 2014;Liu, Fu, Xu, Wang, et al, 2017;Xu, Fu, Norgren, et al, 2018), substorm activities (Cao et al, 2010;Juusola et al, 2011;Ma et al, 2009), and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Busty bulk flows (BBFs) are usually considered to be a consequence of magnetic reconnection in the middle magnetotail and closely associated with substorms. [1][2][3][4][5] As BBFs approach the Earth, they are decelerated by the dominant dipole magnetic field, 1,6 exciting current wedge, and geomagnetic pulsation Pi2. 7,8 A typical phenomenon characterized by a sharp increase in B z at the leading edge of fast flow is referred to as the dipolarization front (DF), which is a thin, vertical current sheet layer that separates tenuous plasma flow from ambient dense plasma in the plasma sheet.…”
Section: Introductionmentioning
confidence: 99%